Brainstem catecholaminergic neurons mediate cognitive impairment in heart failure rats through regulation of hippocampal synaptic-related gene expression - Toledo, Camilo; Martinez, Milka; Diaz, Hugo; Schwartz, Karla; Pereyra, Katherin; Diaz-Jara, Esteban; Del Rio, Rodrigo (My University, 2020)
Heart failure (HF) is common in elder population and it is highly associated with cognitive impairment (CI). Several studies suggest that autonomic imbalance contribute to age‐related CI. We previously showed that catecholaminergic neurons (C1) from the rostral ventrolateral medulla (RVLM) displayed chronic activation in HF. In addition, we also shown that HF rats showed CI. Whether RVLM‐C1 neurons contribute to CI in the setting of HF is completely unknown. Therefore, we aimed to study the contribution of RVLM‐C1 neurons on cognitive function in HF. Adult male Sprague‐Dawley rats underwent volume overload to induce HF. Anti‐dopamine β‐hydroxylase‐saporin (DβH–SAP: 5ng/150nl) was used to selectively destroy RVLM‐C1 neurons. Morris water maze (MWM) test was used to assess learning and memory performance. Micropunches containing the hippocampus were dissected to measure the expression of several synaptic‐related genes using a custom 12‐gene array by qRT‐PCR. HF rats displayed learning and memory impairment compared to control animals. Indeed, HF showed an increased traveled distance to the target platform along 5 trial/days during MWM test (15.1±0.5 vs. 30.7±2.1 m; Control vs. HF, respectively; p<.05). In addition, when the platform was changed daily to a different quadrant (i.e. to evaluate reference memory) HF rats showed an increase in the number of trials required to reach the platform compared to control rats (4.2±0.1 ± vs. 8.2±1.2 trials; Control vs. HF, respectively; p<.05). Partial ablation of RVLM‐C1 neurons in HF rats decreased traveled distance to reach the target platform compared to HF rats without treatment (18.1±1 vs 30.7±2.1 m; HF DβH–SAP vs. HF, respectively; p<.05). Also, during memory testing HF untreated rats needed almost twice the number of trials to accomplish the task when compared to HF+DβH–SAP rats (4.4±0.4 vs. 8.2±1.2 trials; HF DβH–SAP vs. HF, respectively; p<.05). Finally, compared to control rats, HF rats display (Ctrl vs. HF, in AU) decreased levels of PSD‐95 (1.0±0.2 vs. 0.4±0.3), Hommer1 (1.0±0.2 vs. 0.6±0.3), CaMKIV (1.0±0.2 vs. 0.5±0.3), Piccolo (1.0±0.3 vs. 0.4±0.2), Erc2 (1.0±0.3 vs. 0.2±0.1), RIM (1.0±0.5 vs. 0.3±0.2), Neuroligin 3 (1.0±0.4 vs. 0.5±0.3), Neuroxin 1 (1.0±0.3 vs. 0.6±0.4) and Synaptotagmin‐1 (1.0±0.3 vs. 0.6±0.1). Importantly, DβH–SAP treatment in HF significantly restored the expression levels of Hommer1, Piccolo, Erc2, RIM and Synaptotagmin‐1 to levels observed in control rats. Taken together, our results show that catecholaminergic RVLM neurons contribute to CI in HF rats. In addition, our results suggest that RVLM‐C1 may regulate hippocampal synaptic transmission in the setting of HF through the regulation of gene expression in the hippocampus. Support or Funding Information Supported by FONDECYT 1180172 and 3190659 and the basal Center of Excellence in Aging and Regeneration (AFB 170005).
Keywords: Rostral ventrolateral medulla